Perdagangan Intra Industri Kakao Indonesia dengan Negara Mitra: Intra Industry Trade of Indonesian Cocoa with Partner Countries - Andi Tenri Darhyati; Novianti, Tanti (Buletin Ilmiah Litbang Perdagangan, 2023)
Intra-industry trade (IIT) is trade in the same product between one country and another. Cocoa is an Indonesian agricultural commodity that tends to carry out intra-industry trade. This research aims to analyze intra-industry trade relations between Indonesian Cocoa and trading partner countries and the factors that influence intra-industry trade in Indonesian Cocoa. This research uses panel data from a period from 2016-2021. The best model chosen was the Random Effect Model (REM). The analysis method used is the Intra Industry Trade Index and Gravity Model. The results of the analysis show that the country that has strong integration in intra-industry trade in cocoa is Indonesia and Malaysia. IIT in Indonesian cocoa with partner countries is still predominantly weakly integrated. The factors that influence intra-Indonesian cocoa industry trade are the average of Gross Domestic Product (GDP) per capita between countries, differences in GDP between countries, differences in GDP per capita between countries, and foreign direct investment (FDI). The government needs to maintain IIT with Malaysia, which has strong integration and has the potential to increase FDI. Meanwhile, increasing intra-industry trade can be done by considering increased exports and transfer of technology and knowledge.